HUBUNGAN RELIGIUSITAS DENGAN TINDAKAN SKRINING KANKER PAYUDARA PADA WANITA DI WILAYAH KERJA PUSKESMAS PANDAK I BANTUL YOGYAKARTA - Kartika Rukmi, Dwi; Trisetiyaningsih, Yanita; Aryu Brata D, Andria Fistra (MEDIA ILMU KESEHATAN, 2017)
Background: Cancer is one of the leading causes of death worldwide. Breast cancer screening involves breast self-examination (BSE), clinical breast examination (SADANIS), and mammography. The high rates of breast cancer result from the low number of women who screen for breast. As an important thing, religiosity affecting healthy behaviors and illnesses including the cancer screening action are rarely studied. Objective: The objective of this research is to identify the correlation between religiosity with women’s breast cancer screening in the working area of Pandak I Community Health Center, Bantul District, Yogyakarta. Method: This is a correlational analytical research along with a cross sectional approach. This research involved 397 respondents aged 20 years old or older than the age in question and they were not suffering from breast cancer measured by using an accidental sampling technique. The data collection technique was a questionnaire and the data processing dealt with the Spearman Rho. Results: The majority of respondents’ religiosity was moderate (77.3%) and the majority of breast cancer screening measurements was low (59.4%). The Spearman Rho test results showed no relation between religiosity with women’s breast cancer screening action in the working area of Pandak I Community Health Center, Bantul District, Yogyakarta (Pv: 0,938, Sig: 0,05). The Spearman correlation value was 0.004, indicating that the correlation direction was positive along with the weakest correlation strength. Conclusion: Breast cancer screening measurements are low and unrelated to the level of religiosity. The reason for not doing breast cancer screening action largely depends on the belief that health is determined by God. Therefore, nurses should further enhance the promotion of health education regarding breast cancer screening measurements using an approach other than religiosity. Keywords: Breast cancer, religiosity, screening, women